Macular Thickness and Its relation with Age and Gender in Healthy Eyes Using Cirrus-HD Optical Coherence Tomography (Indian Journal of Forensic Medicine & Toxicology, 2020)
Purpose of the Study: To provide a normative data for macular thickness in healthy Iraqi eyes using Zeisscirrus HD-OCT and to determine the effects of age and gender on their measurements.Materials and Methods: Two hundred healthy adult volunteers (?20 years), four hundred eyes underwentmacular cube scanning using Zeiss cirrus-HD OCT. Macular thickness from all 9 regions of the EarlyTreatment Diabetic Retinopathy Study map was documented for each subject. Variations in macularthickness by age and gender were determined.Results: The mean age of volunteers was 37±10.4 (range 21-67)years. The mean of central foveal thicknesswas 254.6±17.3Mm, the mean macular thickness was 279.0 ± 10.7 Mm, and the macular volume was 10.0 ±0.4 mm3.Females were found to have a significantly thinner macula (P< 0.001) than males in all 9 ETDRSregions except outer inferior quadrant. Central foveal thickness was found to have very weak correlationwith age which was not statistically significant. All other macular regions, mean macular thickness andvolume showed statistically significant nonlinear reduction with age(p value
Keywords: Macular Thickness, Healthy Eyes, OCT